2017
DOI: 10.1016/j.vetimm.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mite allergoids coupled to nonoxidized mannan from Saccharomyces cerevisae efficiently target canine dendritic cells for novel allergy immunotherapy in veterinary medicine

Abstract: We have recently reported that grass pollen allergoids conjugated with nonoxidized mannan of Saccharomyces cerevisae using glutaraldehyde results in a novel hypoallergenic mannan-allergen complex with improved properties for allergen vaccination. Using this approach, human dendritic cells show a better allergen uptake and cytokine profile production (higher IL-10/IL-4 ratio) for therapeutic purposes. Here we aim to address whether a similar approach can be extended to dogs using canine dendritic cells. Six hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…We previously demonstrated that PM‐allergoids are much better captured than native allergens by human16 and canine17 DCs and that this property is lost upon mannan oxidation. Here we show that this is also the case in mice when assessing antigen‐presenting cells (CD45 + MHC‐II + ) from the sublingual mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that PM‐allergoids are much better captured than native allergens by human16 and canine17 DCs and that this property is lost upon mannan oxidation. Here we show that this is also the case in mice when assessing antigen‐presenting cells (CD45 + MHC‐II + ) from the sublingual mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of PM‐allergoids, however, their low IgE binding reactivity16, 17, 18 would make this mechanism unlikely. Nevertheless, other IgE‐independent mechanisms for allergen uptake have been described further, like CD207 (Langerin), a putative mannose receptor,32, 33 or CD209 (DC‐SIGN) 34.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations